Effects of Vibratory Stress Relief on Microstructure and Mechanical Properties of Marine Welded Structures - Liqiang Gao; Qinan Yao; Yuchen Yang; Dejian Sun; Guanhua Xu; Bangping Gu; Cong Yang; Shuaizhen Li (Journal of Marine Science and Engineering)
Dissimilar steel welded structures are commonly used in the marine engineering field. Owing to the scarcity of in-depth investigation into the intricate pattern of residual stress distribution in welding within 316L/Q345 dissimilar steel welded joints and methods for reducing this stress, a platform-based vibratory stress relief (VSR) experimental system was established to comprehensively study the effects of VSR on the mechanical properties and microstructure of 316L/Q345 welded structures. Scanning electron microscopy (SEM) was used to examine the fracture morphology and explore the intrinsic mechanisms by which VSR enhances the mechanical properties of welded joints. The findings suggest that VSR is capable of significantly homogenizing and diminishing the welding residual stress within the heat-affected area of 316L/Q345 mismatched steel welded specimens. The significant reduction in residual stress after VSR can primarily be attributed to the combination of alternating stress applied by the VSR platform and the welding residual stress, which exceeded the yield limit of the metal materials. Furthermore, the significant reduction in residual stress, refinement of second-phase particles, and changes in fracture mechanisms are the main reasons for the increased strength observed after VSR. This study has significant engineering application value, providing a theoretical basis for the use of VSR treatment to enhance the reliability of the safe operation of marine engineering equipment.